2019
DOI: 10.1016/j.bpj.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Tension- and Adhesion-Regulated Retraction of Injured Axons

Abstract: Damage-induced retraction of axons during traumatic brain injury is believed to play a key role in the disintegration of the neural network and to eventually lead to severe symptoms such as permanent memory loss and emotional disturbances. However, fundamental questions such as how axon retraction progresses and what physical factors govern this process still remain unclear. Here, we report a combined experimental and modeling study to address these questions. Specifically, a sharp atomic force microscope prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Thus, the faster bond dissociation of these complexes, with or without mechanical forces, makes stimulation of retraction of neuronal processes unlikely. Therefore, Syndecan-4 appears to play a key role in modulating the speed of neuronal responses under pathological conditions ( Figure 5 ), in agreement with the rapid axon retraction observed in vivo ( Houle and Tessler, 2003 ) and in vitro ( Shao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, the faster bond dissociation of these complexes, with or without mechanical forces, makes stimulation of retraction of neuronal processes unlikely. Therefore, Syndecan-4 appears to play a key role in modulating the speed of neuronal responses under pathological conditions ( Figure 5 ), in agreement with the rapid axon retraction observed in vivo ( Houle and Tessler, 2003 ) and in vitro ( Shao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…Here, we studied morphological neuronal changes stimulated by cell-cell communication between neurons and astrocytes through the cell adhesion molecules, Thy-1, α V β 3 integrin and Syndecan-4. It has also been reported that cell-extracellular matrix interactions play a key role in the regulation of neuronal process retraction ( Ahmad et al, 2000 ; Franze et al, 2009 ; Shao et al, 2019 ), as well as in the contraction of other cell types ( Okamoto et al, 1998 ). In our neurite retraction assays, CAD cells were seeded directly over standard tissue culture dishes without additional treatments (e.g., poly- L -lysine).…”
Section: Discussionmentioning
confidence: 99%
“…There thus appear to be at least two processes that account for the optimum-curve like distribution of regenerative capacity (see Fig. 5): First, the reduced capacity after injury very close to the soma might be due to an initial axonal retraction response (also known as axonal dieback) that has been suggested (after injury set with different methods) in other systems 47,48 . Second, additional processes must account for the decay of regenerative capacity farther away from the soma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28,29 ] Accordingly, subsequent reduction of these actomyosin tugging forces results in shrinkage and loss of FAs. [ 30,31 ] In contrast, other mechano‐adaptions can persist long past cessation of the original mechanical cue, resulting in lasting or even permanent changes in cell behavior; this is well illustrated by work from the Hinz and Anseth groups. The former showed that fibroblasts could be “activated” to a myofibroblast phenotype by culture on a stiff substrate, and that this transformation persisted through multiple population doublings, even after the cells were returned to a soft environment.…”
Section: Mechanotransduction and Mechanical Memorymentioning
confidence: 99%